A Model for Standardized and Proactive Advance Care Planning. Issue 1 (2nd January 2022) - Hage, Martha; Nelson, Eric; Bocchino, Amy; Ginsberg, Jessica; Potter, Jordan
Abstract: As the importance of Advance Care Planning (ACP) has become well-known and accepted, health systems have begun placing more emphasis on ACP. However, many health systems still have not standardized this process, and most health systems still approach ACP in a reactive—rather than proactive—manner. This paper discusses one system's innovative approach to ACP that standardizes ACP in the inpatient and outpatient settings, while focusing on a proactive rather than reactive orientation to ACP.